Does government support matter in the relationship between future orientations on women’s effective leadership - Gorondutse, Abdullahi Hassan; Al Shdaifat, Fayez Hamed; Abdullah, Haim Hilman; Alajmi, Rajeh; Ahmed, Fais (Emerald Group Publishing Limited, 2021)
The purpose of this paper is to understand emerging future orientations, women’s effective leadership and further examine its impact on government support in the context of higher education institutions. A cross-sectional survey with 500 full-time women employees, working in Saudi Arabia Public University, was selected using a quantitative approach and analysed on the proposed hypotheses. The initial prediction was that future orientations is significant on women’s leadership effectiveness as well as on government support, to the extent that it is associated with women’s leadership effectiveness where it tends to have a stronger relationship. Surprisingly, the indirect effect of government support on the relationship between future orientations on women’s leadership effectiveness was not significant. Academic scholars/leaders in higher education should realize that the development of women leadership has a positive effect on future orientations. Policymakers and leaders of higher education institutions should focus on women leaders to improve their leadership effectiveness. From the perspective of emerging nations, this paper extends the knowledge regarding the complexity leadership theory which explains the development of women’s leadership effectiveness and provides empirical evidence.